An Automated and Robust Tool for Musculoskeletal and Finite Element Modeling of the Knee Joint - Esrafilian, Amir; Chandra, Shekhar S.; Gatti, Anthony A.; Nissi, Mikko J.; Mustonen, Anne-Mari; Saisanen, Laura; Reijonen, Jusa; Nieminen, Petteri; Julkunen, Petro; Toyras, Juha; Saxby, David J.; Lloyd, David G.; et al. (IEEE transactions on biomedical engineering, 2025)
Objective: To develop and assess an automatic and robust knee musculoskeletal finite element (MSK-FE) modeling pipeline. Methods: Magnetic resonance images (MRIs) were used to train nnU-Net networks for auto-segmentation of knee bones (femur, tibia, patella, and fibula), cartilages (femur, tibia, and patella), menisci, and major knee ligaments. Two different MRI sequences were used to broaden applicability. Next, we created MSK-FE models of an unseen dataset using two MSK-FE modeling pipelines: template-based and auto-meshing. MSK models had personalized knee geometries with multi-degree-of-freedom elastic foundation contacts. FE models used fibril-reinforced poroviscoelastic swelling material models for cartilages and menisci. Results: Volumes of knee bones, cartilages, and menisci did not significantly differ ( p >0.05) across MRI sequences. MSK models estimated secondary knee kinematics during passive knee flexion tests consistent with in vivo and simulation-based values from the literature. Between the template-based and auto-meshing FE models, estimated cartilage mechanics often differed significantly ( p <0.05), though differences were <15% (considering peaks during walking), i.e., <1.5 MPa for maximum principal stress, <1 percentage point for collagen fibril strain, and <3 percentage points for maximum shear strain. Conclusion: The template-based modeling provided a more rapid and robust tool than the auto-meshing approach, while the estimated knee biomechanics were comparable. Nonetheless, the auto-meshing approach might provide more accurate estimates in subjects with distinct knee irregularities, e.g., cartilage lesions. Significance: The MSK-FE modeling tool provides a rapid, easy-to-use, and robust approach for investigating task- and person-specific mechanical responses of the knee cartilage and menisci, holding significant promise, e.g., in personalized rehabilitation planning.